Is the diagnostic radiological image an underutilised resource? Exploring the literature - William A. S. Cox; Penelope Cavenagh; Fernando Bello (Insights into Imaging, 2019)
Abstract The number of diagnostic imaging examinations being undertaken in the UK is rising. Due to the expensive nature of producing these examinations and the risks associated with exposing living tissue to the ionising radiation used by many of the imaging techniques, this growth comes with both a financial and a human cost. In a time of limited resources, it is important that we are able to maximise the benefits which we extract from these resources. Therefore, a broad search of the current literature was undertaken to assess our current understanding of the nature of benefit available from diagnostic radiological images. Two broad categories of benefit were identified: primary benefit (n = 470) and secondary benefit (n = 49). Primary benefits are those which are related to the justification for undertaking the imaging, e.g., abnormality detection, to assist in diagnosis or staging, or acting as an aid to clinical decision making, or intervention. Secondary benefits are those that are not related to the justification for imaging, e.g., to promote patient engagement and understanding or to facilitate communication. Existing work considering primary benefits is comprehensive. Secondary benefit, however, is less well recognised and may not be reliably realised. Use of the image to realise these benefits has far-reaching potential. Particularly, there may be underexplored benefits which access to the images may provide to patients. This represents a gap in existing research which should be addressed.